Gestational Weight Gain and Breastfeeding Outcomes in Group Prenatal Care. (18th July 2016) - Brumley, Jessica; Cain, M. Ashley; Stern, Marilyn; Louis, Judette M.
Abstract : Introduction: This study sought to examine the differences in pregnancy outcomes with a focus on gestational weight gain for women attending group prenatal care compared to standard individual prenatal care. Methods: A matched case‐control study was conducted including 65 women who chose group care and 130 women who chose standard individual care. Women were matched based on prepregnancy body mass index (BMI) category, eligibility for midwifery care, and age within 5 years. Results: Women choosing group prenatal care and women choosing standard individual care had similar gestational weight gain, birth weight, gestational age at birth, and mode of birth. Women choosing group prenatal care did have a significantly higher rate of exclusive breastfeeding at 6 weeks postpartum (odds ratio [OR], 4.07; 95% confidence interval [CI], 1.81‐9.15; P < .001) than women choosing individual care. Discussion: Group prenatal care participation resulted in equivalent gestational weight gain as well as pregnancy outcomes as compared to standard individual care. Breastfeeding rates were improved for women choosing group prenatal care. Randomized controlled trials are needed in order to eliminate selection bias.